Evaluating total carrying capacity of tourism using impact indicators - R. Sharma (Global Journal of Environmental Science and Management)
The carrying capacity is well identified tool to manage problems due to uncontrolled tourism for any destination. This report highlights the carrying capacity estimation of Kerwa tourism area, Bhopal, India. The methodology used in this report is a new two-tier mechanism of impact analysis using index numbers derived from a survey of 123 stakeholders. From this the individual component impact analysis and the total carrying capacity of the area is computed in order to state the insight of the total carrying capacity left for the tourism activities in Kerwa tourism area. It is calculated from, the results so obtained, that the Kerwa catchment area falls in “very low impact category” and hence in a healthy state of the artwork in terms of total carrying capacity. The study conveys the current need in the destination management and tourism development as a road map for the destination managers for implementing sustainable tourism.